2021
DOI: 10.17159/2078-516x/2021/v33i1a10864
|View full text |Cite
|
Sign up to set email alerts
|

24 hour movement behaviours and the health and development of pre-school children from Zimbabwean settings: the SUNRISE pilot study

Abstract: Background: In 2019, the World Health Organization (WHO) released global guidelines for physical activity, sedentary behaviour and sleep for the early years. The International Study of Movement Behaviours in the Early Years, SUNRISE, aimed to assess the extent to which children aged three and four years meet the WHO global guidelines and its association with health and development. Objectives: To assess movement behaviours in pre-school children from low-income settings in Zimbabwe and to establish association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
3
3
1
Order By: Relevance
“…A possible reason is that a higher proportion of Ethiopian children met the physical activity and sleep guidelines. These ndings are consistent with earlier studies regarding compliance with physical activity [4,11,15,18,19], sleep [4-6, 15, 18] and sedentary behaviour guidelines [5,13,15].…”
Section: Adherence To the Who 24-hour Movement Behaviours Guidelinessupporting
confidence: 93%
See 3 more Smart Citations
“…A possible reason is that a higher proportion of Ethiopian children met the physical activity and sleep guidelines. These ndings are consistent with earlier studies regarding compliance with physical activity [4,11,15,18,19], sleep [4-6, 15, 18] and sedentary behaviour guidelines [5,13,15].…”
Section: Adherence To the Who 24-hour Movement Behaviours Guidelinessupporting
confidence: 93%
“…Our study found that there was no signi cant difference between boys and girls in meeting the individual and combined WHO guidelines. These ndings were consistent with several previous studies [9,14,15,19]. Conversely, our results were in contrast with some evidence reported for combined [21,43], physical activity [22,43] and sleep [43].…”
Section: Adherence To the Who 24-hour Movement Behaviours Guidelinessupporting
confidence: 90%
See 2 more Smart Citations
“…In the urban setting, none of the preschoolers, independent of age, comply with the three recommendations simultaneously, which is under the 3% we previously observed in a similar Brazilian urban context (de Lucena Martins et al, 2021). In analogous low‐middle income backgrounds, pilot studies conducted with South African (Draper et al, 2020), Zimbabwean (Munambah et al, 2021), and Vietnamese (Kim et al, 2022) children reported 26%, 24%, and 17.5% compliance with the overall guidelines, respectively. Moreover, in the three contexts, South African ( n = 77), Zimbabwean ( n = 81), and Vietnamese ( n = 103) preschoolers were highly compliant with PA guidelines (84%, 92%, and 50.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%